Biphasic activity of cd137 ligand-stimulated monocytes on T cell apoptosis and proliferation - Shaqireen Kwajah, M.; Mustafa, N.; Holme, A.; Pervaiz, Shazib; Schwarz, H. (Society for Leukocyte Biology, 2011)
CD137L (4-1BBL) is a member of the TNFSF and is expressed on APCs as a transmembrane protein. Reverse signaling by CD137L in monocytes causes cell activation and differentiation to mature inflammatory DCs that can stimulate T cell proliferation. However, CD137L agonists have also been reported to induce apoptosis in PBMCs. This study aimed at clarifying these seemingly opposing activities. We find that the dying cells within PBMCs are T cells and that this T cell death is dependent on monocytes and correlates with the monocyte:T cell ratio. This CD137L-induced, monocytemediated T cell apoptosis is reminiscent of MDCD, and both are cell contact-dependent. T cell death is not mediated by CD95 or DR4 or -5 but by ROS produced by the T cells. T cell apoptosis is restricted to the first 24 h of stimulation, and at later time-points, the monocytes differentiate to inflammatory DCs under the influence of CD137L signaling and acquire the capacity to stimulate T cell proliferation from Day 4 onward. This biphasic activity may contribute to infection-induced T cell attrition, where in the early phase (<24 h) of an infection, massive T cell apoptosis occurs before the antigen-specific T cells expand. © Society for Leukocyte Biology.